1997
DOI: 10.1001/archpsyc.1997.01830180067009
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine in Patients With Schizophrenia

Abstract: Quetiapine is an effective antipsychotic with a favorable safety profile. The optimum dose is probably greater than 250 mg/d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(50 citation statements)
references
References 17 publications
1
46
0
1
Order By: Relevance
“…For the BPRS total score, first a superiority test was done and, if the null hypothesis was not rejected, a secondary non-inferiority hypothesis was tested with a non-inferiority limit set at six points considered clinically relevant with regards to the placebo-active drug difference generally observed (Chouinard et al 1993;Marder and Meibach 1994;Beasley et al 1996a,b;Van Kammen et al 1996;Arvanitis et al 1997;Small et al 1997;Zimbroff et al 1997;Peuskens et al 1999). All other efficacy parameters were analyzed using 2-sided tests for superiority.…”
Section: Discussionmentioning
confidence: 99%
“…For the BPRS total score, first a superiority test was done and, if the null hypothesis was not rejected, a secondary non-inferiority hypothesis was tested with a non-inferiority limit set at six points considered clinically relevant with regards to the placebo-active drug difference generally observed (Chouinard et al 1993;Marder and Meibach 1994;Beasley et al 1996a,b;Van Kammen et al 1996;Arvanitis et al 1997;Small et al 1997;Zimbroff et al 1997;Peuskens et al 1999). All other efficacy parameters were analyzed using 2-sided tests for superiority.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been several studies that have examined the effect of antipsychotics or adjunctive agents for persistent negative symptoms. In these studies, when an effect has been observed, it has always been observed within the time frame of the current study (Paillère-Martinot et al 1995;Heresco-Levy et al 1996;Goff et al 1995b;Marder and Meibach 1994;Tollefson et al 1997;Small et al 1997).…”
Section: Discussionmentioning
confidence: 60%
“…Quetiapine fumarate is a serotonine and dopamine receptor antagonist used to treat schizophrenia and belongs to the same family as clozapine and olanzapine, which are classified as atypical antipsychotics [1]. Its chemical designation is 2-(2- [4-(dibenzo[b,f] [1,4]thiazepine-11-yl)piperazin-1-yl]ethoxy) ethanol fumarate (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Its chemical designation is 2-(2- [4-(dibenzo[b,f] [1,4]thiazepine-11-yl)piperazin-1-yl]ethoxy) ethanol fumarate (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%